Dual and Plural Terms: Semantic and Grammatical Study - Al-Rabei, Hamoud bin Hammad (Arts for Linguistic & Literary Studies, 2021)
This research discusses patterns of discourse extracted from what was extracted from the base in the singular, dual and plural, trying to follow the semantic direction of these patterns and studying the grammatical approach. The research was opened with an introduction and a brief preface of the origin of the term and its semantics. The study then reviewed the patterns extracted from the base in the singular, the dual and the plural, and it is has ended with a conclusion that includes the most important results. The most prominent results are: that the base is the use of each subject, and does not come out of it, even if quoted any of this to offset the semantics, and mixed topics. The measuring them will lead to the demolition of the rules and proof of the provisions of things that its interpretation is possible. The best thing is limiting patterns out of the base from the audio, and that the use of the researcher for the discourse of plural is not valid; because the used principals of the Arabs is that the individual becomes as a combination with it, contrary to what is claimed that it carries the participation meaning; this is not its place.